Peningkatan Kompetensi Digital Marketing Bagi Wirausaha Muda Di Kota Bengkulu - Tarigan, Heskyel Pranata; Khofifah, Fitri (Jurnal Gotong Royong, 2026)
The development of digital technology has brought about significant changes in the world of marketing, requiring businesses to possess digital marketing skills to enhance their competitiveness. Young entrepreneurs, as part of the creative economy, need to be competent in utilizing digital media as a means of product promotion and marketing. This community service activity aims to improve the digital marketing competency of young entrepreneurs in Bengkulu City through digital marketing education and training. The activity implemented through counseling, practical training, discussions, and mentoring related to the use of social media, promotional content creation, branding strategies, and the use of digital marketplaces. Participants consisted of young entrepreneurs with micro and small businesses in Bengkulu City. The results of the activity showed that participants experienced an increase in understanding and skills in using digital platforms as a product marketing medium. In addition, participants were also able to create more engaging promotional content and understand effective digital marketing strategies to increase consumer reach. This activity has a positive impact on increasing the knowledge, creativity, and readiness of young entrepreneurs to face business competition in the digital era. Therefore, digital marketing education and mentoring need to be carried out continuously so that young entrepreneurs can develop their businesses optimally through the use of digital technology.